2020
DOI: 10.1080/14616688.2020.1801828
|View full text |Cite
|
Sign up to set email alerts
|

Cultural ecosystem services evaluation using geolocated social media data: a review

Abstract: Reducing private car use is an efficient way to promote the sustainable development of national parks.However, many visitors persist in using their cars, even when they are aware of the environmental damage it causes.This study proposed a norm-neutralization model to investigate why national park visitors persist in car-based trips by partially integrating the theory of planned behavior, the norm-activation model, and neutralization theory. The results indicated that neutralization techniques can effectively r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 105 publications
0
27
0
Order By: Relevance
“…Compared to other information gathering methods and techniques, such as interviews or surveys, they are based on user behavior and, as such, are less exposed to the biases of social desirability. The most photographed places usually show the preferences of the visitors, and more specifically, the density of geolocated content correlates with the number of visits (Zhang et al, 2020). In our study, we have observed that the centralization of the tag network is inversely related to the diversity of ecosystem uses associated with the environment.…”
Section: Natural Values and Subjective Assessment Of The Landscapementioning
confidence: 50%
See 1 more Smart Citation
“…Compared to other information gathering methods and techniques, such as interviews or surveys, they are based on user behavior and, as such, are less exposed to the biases of social desirability. The most photographed places usually show the preferences of the visitors, and more specifically, the density of geolocated content correlates with the number of visits (Zhang et al, 2020). In our study, we have observed that the centralization of the tag network is inversely related to the diversity of ecosystem uses associated with the environment.…”
Section: Natural Values and Subjective Assessment Of The Landscapementioning
confidence: 50%
“…The extraction of digital data is not based on obtaining representative samples of the population but on the exhaustive collection of photographs and tags. Indeed, the number of photos associated with a geographical location is one of the most used indicators in the evaluation and management of ecosystems (Zhang et al, 2020). The analysis of social networks also does not follow the logic of sampling in the collection, analysis, and interpretation of data.…”
Section: Discussionmentioning
confidence: 99%
“…Our work demonstrated that the social media data on CES greatly extends the type and, especially, the volume and scale of information that can be derived from traditional survey methods (Retka et al 2019; Zhang et al 2020). However, the data from this study were limited, as only blog texts from social media platforms were analyzed.…”
Section: Discussionmentioning
confidence: 67%
“…The public's experiences in the park were inductively identi ed and categorized into ve experience dimensions: animal, nature, scenery, engagement and culture. These categories are often used in photo content analysis across social media studies, with slight differences in the dimension names (Zhang et al 2020;Richards and Tunçer 2017;Callau et al 2019;Tenerelli et al 2016;Richards and Friess 2015;Retka et al 2019;Hale et al 2019). For example, the animal dimension has been labelled as "wildlife" or "biodiversity"; nature has been labelled as " plants" or "natural landscape"; engagement has been labelled as "physical use of landscape", "people", "social recreation", "artistic or cultural expressions and appreciation", or "emotional reactions"; scenery has been labelled as "landscape" or "aesthetic"; and culture has been labelled as "cultural heritage", "infrastructure appreciation" "history", or "sense of place".…”
Section: Discussionmentioning
confidence: 99%